2013
DOI: 10.1152/ajpendo.00439.2012
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycemic control in mice lacking Sglt1 and Sglt2

Abstract: Sodium-glucose cotransporter 2 (SGLT2) is the major, and SGLT1 the minor, transporter responsible for renal glucose reabsorption. Increasing urinary glucose excretion (UGE) by selectively inhibiting SGLT2 improves glycemic control in diabetic patients. We generated Sglt1 and Sglt2 knockout (KO) mice, Sglt1/Sglt2 double-KO (DKO) mice, and wild-type (WT) littermates to study their relative glycemic control and to determine contributions of SGLT1 and SGLT2 to UGE. Relative to WTs, Sglt2 KOs had improved oral gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
150
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 59 publications
16
150
0
Order By: Relevance
“…However, maximally effective SGLT2 inhibitor doses typically prevent ;50% of the filtered glucose from being reabsorbed, suggesting that SGLT1 has considerably greater capacity for glucose reabsorption than expected based on the commonly quoted 90% value for SGLT2. This is supported by data from genetic models, since SGLT2 KO mice exhibit only about 30% of the UGE observed in SGLT1/SGLT2 double KO mice (17). These data, combined with human care.diabetesjournals.orgdata showing that phlorizin can block virtually all renal glucose reabsorption (19), suggest that dual SGLT1/2 renal inhibitors might achieve considerably greater UGE than selective SGLT2 inhibitors.…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, maximally effective SGLT2 inhibitor doses typically prevent ;50% of the filtered glucose from being reabsorbed, suggesting that SGLT1 has considerably greater capacity for glucose reabsorption than expected based on the commonly quoted 90% value for SGLT2. This is supported by data from genetic models, since SGLT2 KO mice exhibit only about 30% of the UGE observed in SGLT1/SGLT2 double KO mice (17). These data, combined with human care.diabetesjournals.orgdata showing that phlorizin can block virtually all renal glucose reabsorption (19), suggest that dual SGLT1/2 renal inhibitors might achieve considerably greater UGE than selective SGLT2 inhibitors.…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 68%
“…In humans, familial renal glucosuria is a rare, benign condition arising from SGLT2 mutations that reduce renal glucose reabsorption and lead to UGE ranging from 1 to 170 g/day, whereas SGLT1 mutations only mildly increase UGE (17). Similarly, only minimal UGE is observed in SGLT1 knockout (KO) mice, whereas high UGE is seen in SGLT2 KO mice (17,18).…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were not observed in SGLT2 knockout mice, confirming that they were the result of decreased SGLT1 and not SGLT2. 10 The experience with SGLT1 knockout mice also provided a perspective on safety. SGLT1 knockout mice maintained on a diet containing glucose and galactose exhibited unformed or watery stools, decreased food intake and reduced weight gain, which provided additional evidence that complete inhibition of intestinal SGLT1 might not be desirable.…”
Section: Background and Conception Of Sotagliflozinmentioning
confidence: 99%
“…However, recent studies in combined SGLT-1/SGLT-2 knockout mice suggest that SGLT-1 is responsible for a much greater reabsorption of the filtered glucose load than previously appreciated. 83 Studies in mice treated with the nonabsorbable SGLT-1 inhibitor LX 2761 (Lexicon) demonstrated reductions in FPG and PPG and a reduction in A1C of 0.7% with no GI side effects, no increase in glucosuria, and an increase in circulating levels of GLP-1 and peptide YY (PYY), hormones that suppress the appetite. 84 With respect to the increase in GLP-1, reduced GI absorption of glucose leads to increased distal delivery of glucose and short-chain fatty acids (produced by bacterial metabolism of glucose in the GI tract), both of which enhance GLP-1 and PYY secretion by the L-cell.…”
Section: Sglt-2 and Sglt-1 Inhibitorsmentioning
confidence: 99%